(untitled) (Vallis Aurea, 2024)
Purpose:The purpose of this study is to investigate the reasons why DevOps engineers utilize cloud optimization technologies. The goal is to help decision-makers improve the utilization of cloud technology, ensure cost-effectiveness, and simplify management within the organization. Design: Two hundred individuals were randomly selected from a pool of eight hundred DevOps experts for quantitative research. Ethical issues were given top priority throughout the study process. Methodology: Rigorous regression and correlation studies were carried out with a 95% confidence level. The study delved into significant correlations between independent factors and the company’s cloud optimisation. Approach: The study focused on reducing maintenance costs, improving scalability, and efficient resource utilisation as major goals. Participants emphasised the significance of cost savings, scalability, and simpler management. Findings: The research showed significant correlations between independent factors and the company’s cloud optimisation.The findings suggest that firm decision-makers focus on reducing maintenance costs, improving scalability, and efficiently utilizing resources to help their DevOps teams successfully use cloud optimization technologies. Originality:The study offers practical recommendations for organizational tactics that promote the efficient use of cloud technologies.It illuminates the unique preferences of DevOps engineers regarding cloud optimisation technologies.